Out-of-pocket expenditures in hospitalized COVID-19 patients: A systematic review and meta-analysis - Ahmad Dehghani Ahmadabad; Sayyed Morteza Hosseini_Shokouh; Parisa Mehdizadeh; Mohammad Meskarpour_Amiri (Wolters Kluwer Medknow Publications, 2024)
The outbreak of COVID-19 has led to substantial out-of-pocket (OOP) expenditures for households during treatment. This study aimed to investigate the OOP expenditures among hospitalized patients with COVID-19 through a systematic review and meta-analysis. A systematic review and meta-analysis were conducted following the PRISMA guidelines. Articles were retrieved from the PubMed, Scopus, and Google Scholar in the period of 2019-2022 and evaluated for quality using the STROBE guidelines. Homogeneity was assessed using the I2 index, and publication bias was examined using a funnel plot. Meta-analysis was performed using Stata 16. Results of the study have shown that a total of nine articles were included in the meta-analysis. The average OOP expenditure for hospitalized COVID-19 patients was found to be US $308.25 (95% CI: 4.17-620.67). The highest OOP expenditure was reported by CHAU (2021) (US $3171.28), followed by GRAG (2022) (US $1582.38), and the lowest by KOTWANI (2021) (US $56.35). According to the results obtained Significant inequality was observed in the OOP expenditures across different countries. Consistent policy recommendations should be made in international forums to reduce these costs in future pandemics for patients in both developed and developing nations.